Scaling-Down Teaching and Research Indicators is Crucial to Define the Holistic Performance of Universities - Rubén Regueira; Gumersindo Feijoo (Universitas Diponegoro, 2023)
This article proposes a two-dimensional model that allows for the evaluation of teaching and research based on quantitative indicators. Regarding teaching performance, the hours of face-to-face classes and those of supervised theses were considered. In the case of research activity, several indicators were proposed (e.g. books and book chapters, articles in JCR journals, patents and translations), which allow for the application to multiple academic disciplines in the fields of Arts & Humanities, Science, Engineering, Health Sciences and Social & Legal Sciences. Our model has been applied to 119 academic disciplines in the 2010s and the results obtained were analyzed under various perspectives: (i) performance timeline, (ii) comparative analysis among different academic disciplines, (iii) scale-down of the analysis to diverse units (e.g. departments, research groups), as well as to the quantification of the individual effort of each faculty member, and (iv) gender perspective. As a model use case, the Department of Chemical Engineering at the University of Santiago de Compostela (USC) was studied. One of the key takeaways of this analysis was that understanding teaching and research reference levels is crucial in defining university-specific targets, both individually and collectively. In fact, this is even more relevant for less hierarchical and more assembly-based academic institutions, where it is difficult to define a minimum standard of research activity.